Respuesta :
First, we find the slope of the line using the points.
[tex] m = \dfrac{y_2 - y_1}{x_2 - x_1} [/tex]
[tex] m = \dfrac{-3 - 11}{1 - (-3)} [/tex]
[tex] m = \dfrac{-14}{4} [/tex]
[tex] m = -\dfrac{7}{2} [/tex]
Now we use the point-slope equation of a line.
[tex] y - y_1 = m(x - x_1) [/tex]
[tex] y - 11 = -\dfrac{7}{2}(x - (-3)) [/tex]
[tex] y - 11 = -\dfrac{7}{2}(x + 3) [/tex]
[tex] 2y - 22 = -7x - 21 [/tex]
[tex] 7x + 2y = 1 [/tex]
Answer: Choice B)
[tex] m = \dfrac{y_2 - y_1}{x_2 - x_1} [/tex]
[tex] m = \dfrac{-3 - 11}{1 - (-3)} [/tex]
[tex] m = \dfrac{-14}{4} [/tex]
[tex] m = -\dfrac{7}{2} [/tex]
Now we use the point-slope equation of a line.
[tex] y - y_1 = m(x - x_1) [/tex]
[tex] y - 11 = -\dfrac{7}{2}(x - (-3)) [/tex]
[tex] y - 11 = -\dfrac{7}{2}(x + 3) [/tex]
[tex] 2y - 22 = -7x - 21 [/tex]
[tex] 7x + 2y = 1 [/tex]
Answer: Choice B)